Shifts in Eighth-Grade Students' Mental Model Levels in Understanding Quadrilateral Concepts Through Group Discussion - Lady Agustina; Sudahri Sudahri (Jurnal Pendidikan Terapan, 2026)
Purpose:  The purpose of this study is to observe how the mental level of the student model experiences a shift in understanding the concept of a quadrangle through the process of group discussion. Methods: This study uses a qualitative approach involving 150 grade VIII students who have previously studied quadrilateral material. A written test on the concept of a quadrangle was given to all participants to determine the initial mental level of their model before the group discussion was conducted. Findings: Preliminary results showed that 12 students were at the initial level, 65 students at the first transition, 52 students at the synthetic level, 18 students at the II transition, and 3 students at the formal level. After the group discussion process, there was a shift in the mental level of the model in several subjects, namely two students from the initial level shifted to the synthetic level; one student from transition I to synthetic; one student from transition I to transition II; and two students from the synthetic level to transition II. Meanwhile, two students at the transition level II and two students at the formal level did not experience a shift. Research implications: These findings suggest that group discussions have the potential to facilitate the mental restructuring of students' models in understanding geometry concepts, especially quadrangles. In addition, this research emphasizes the importance of social interaction in helping students move from intuitive understanding to more formal understanding. Originality: This research contributes by mapping in detail the shift in the mental level of the student model after the group discussion, as well as offering empirical evidence regarding the effectiveness of discussion as a pedagogical strategy in learning geometry concepts.